Fouling and cleaning of high permeability forward osmosis membranes. (February 2016) - Blandin, Gaetan; Vervoort, Harm; Le-Clech, Pierre; Verliefde, Arne R.D.
Graphical abstract: Highlights: Severe fouling occurs when operating with novel high permeability TFC membrane. FO fouling is more related to initial flux than to TFC membrane surface properties. Evidence of a critical flux is demonstrated in FO. Extended osmotic backwashing allows for complete cleaning of fouled membranes. Abstract: This study critically assesses the fouling behavior in forward osmosis (FO) when operating with new generation of high permeability commercial thin film composite (TFC) FO membranes. Low fouling behavior, commonly accepted in FO with the membrane active layer facing the fouling feed solution (AL-FS), is demonstrated to be mainly the consequence of operating at a low permeation flux (typically lower than 10 L m −2  h −1 ). A higher water flux is observed to lead to severe fouling when using high permeability novel TFC membranes. Advanced membrane surface characterisation and FO fouling experiments over a range of initial fluxes (5–17 L m −2  h −1 ) demonstrate that the intense fouling behavior of high permeability TFC membranes is mainly connected to the initial flux, whereas membrane surface properties only play a minor role. Like for any membrane processes, it is demonstrated that a (so-called critical) flux can be defined in FO systems operated in AL-FS, above which stable operation cannot be maintained over an extended period of time. At higher flux, the fouling cake deposed on the active layer creates additional hydraulic resistance to filtration and consequently significant flux decline is observed over time. A typical anti-fouling strategy, such as high cross flow velocity cleaning, is not efficient to sustain high flux, but fouled membranes can be successfully cleaned using extended osmotic backwashing.